Pengaruh Kombinasi Progressive Muscle Relaxation dan Slow Deep Breathing Exercise terhadap Kinesiophobia pada Pasien Rawat Jalan di Surabaya - Pusbagijo Pusbagijo; Achmad Fariz; Rachma Putri Kasimbara; Yohanes Deo Fau (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Kinesiophobia is an excessive fear of physical activity or movement so that patients tend to avoid moving their painful limbs. Not many longitudinal studies have reported that progressive muscle relaxation (PMR) and slow deep breathing exercise (SDBE) have a direct impact on the level of Kinesiophobia. Therefore, we explored the effect of a combination of progressive muscle relaxation and slow deep breathing exercise on kinesiophobia in outpatients with chronic musculoskeletal pain in Surabaya.Methods: This study had 43 respondents who all completed a randomized controlled trial (RCT) for 5 weeks, 21 respondents were randomized to receive a combination of progressive muscle relaxation and slow deep breathing exercise and received standard physiotherapy interventions, while the control group consisted of 22 respondents only with standard physiotherapy interventions. The Tampa Scale of Kinesiophobia (TSK) is used to assess the level of Kinesiophobia experienced by patients.Results: 1. In the experimental group that was given a combination of progressive muscle relaxation and slow deep breathing exercise and standard physiotherapy, the initial mean score without the scale of kinesiophobia (TSK) was 51.73 points, and after the intervention it was 42.32 points.2. As for the control group which was only given standard physiotherapy intervention, the initial average score without the scale of kinesiophobia (TSK) was 51.71 points, and after the intervention it became 48.33 points.3. The Effect of a Combination of Progressive Muscle Relaxation and Slow Deep Breathing Exercise on Kinesiophobia in Outpatients in Surabaya, with a p-value = (p <0.05).Conclusion: The combined progressive muscle relaxation (PMR) and slow deep breathing exercise (SDBE) combination technique is safe to apply to patients with Kinesiophobia disorder because it has relatively no side effects and is practical in its application. The findings from this study support that combination therapy of progressive muscle relaxation (PMR) and slow deep breathing exercise (SDBE) offers beneficial outcomes for patients experiencing chronic pain, as well as for preventing and treating Kinesiophobia.